2003
DOI: 10.1016/s1534-5807(03)00187-4
|View full text |Cite
|
Sign up to set email alerts
|

Unequal Segregation of Neuralized Biases Notch Activation during Asymmetric Cell Division

Abstract: In Drosophila, Notch signaling regulates binary fate decisions at each asymmetric division in sensory organ lineages. Following division of the sensory organ precursor cell (pI), Notch is activated in one daughter cell (pIIa) and inhibited in the other (pIIb). We report that the E3 ubiquitin ligase Neuralized localizes asymmetrically in the dividing pI cell and unequally segregates into the pIIb cell, like the Notch inhibitor Numb. Furthermore, Neuralized upregulates endocytosis of the Notch ligand Delta in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
266
1
10

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 227 publications
(281 citation statements)
references
References 38 publications
4
266
1
10
Order By: Relevance
“…While previous clonal studies have indicated that neur is required for lateral inhibition (Yeh et al 2000;Le Borgne and Schweisguth 2003), the influence of neur gene dosage on sensory cell fate has not been studied. A role for Neur during competition is not necessarily expected since neur transcripts and Neur proteins have been detected in SOPs but not in PNC cells (Boulianne et al 1991;Le Borgne and Schweisguth 2003). Indeed, this expression pattern suggests that neur may only act in singled out SOPs to reinforce lateral signaling and that it does not act when PNC cells still compete for the SOP fate.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…While previous clonal studies have indicated that neur is required for lateral inhibition (Yeh et al 2000;Le Borgne and Schweisguth 2003), the influence of neur gene dosage on sensory cell fate has not been studied. A role for Neur during competition is not necessarily expected since neur transcripts and Neur proteins have been detected in SOPs but not in PNC cells (Boulianne et al 1991;Le Borgne and Schweisguth 2003). Indeed, this expression pattern suggests that neur may only act in singled out SOPs to reinforce lateral signaling and that it does not act when PNC cells still compete for the SOP fate.…”
Section: Resultsmentioning
confidence: 99%
“…The activity of Dl is positively regulated at the posttranscriptional level by the E3 ubiquitin ligase Neuralized (Neur) and Neur-dependent Dl signaling is essential for proper SOP specification (Boulianne et al 1991;Lai et al 2001;Pavlopoulos et al 2001;Le Borgne and Schweisguth 2003;Le Borgne et al 2005). Recent studies have shown that regulation of Dl activity by Neur is antagonized by proteins of the Bearded (Brd) family.…”
mentioning
confidence: 99%
“…Furthermore analysis of zebrafish mutants uncovered Mind bomb as an ubiquitin ligase required for Delta endocytosis and this was followed by the observation of similar proteins in Drosophila (Neuralized and D-Mind bomb 1 and 2). These proteins act on Delta to promote ubiquitination and endocytosis and thus enhance the signalling ability of the signal-sending cells (Pavlopoulos et al 2001, Le Borgne & Schweisguth 2003, Itoh et al 2003, Lai et al 2005, Bardin & Schweisguth 2006. Ubiquitination of the DSL ligands makes them targets of adaptor proteins such as liquid facets (Lqf, a homologue for epsin) which promotes endocytosis (Wang & Struhl 2004.…”
Section: Ligand Traffickingmentioning
confidence: 99%
“…The best characterized function of Notch is probably 'lateral inhibition', a process of central importance in the assignation of cell fates and their spatial patterning (Heitzler & Simpson 1993, Le Borgne & Schweisguth 2003, Gibert & Simpson 2003. The notion of lateral inhibition is derived from the observation that during development, groups of cells emerge that are assigned a common developmental potential but only some cells within the group adopt that potential.…”
Section: Lateral Inhibitionmentioning
confidence: 99%
See 1 more Smart Citation